Ultrastructure of the egg of Coquillettidia venezuelensis (Theobald) (Diptera: Culicidae) - de Mello, Cecilia Ferreira; Alencar, Jeronimo (Zootaxa, 2020)
This study examined the ultrastructural characteristics of the egg of Coquillettidia venezuelensis (Theobald) (Diptera: Culicidae) with the aid of scanning electron microscopy. The eggs are elliptical and blackish, measuring on average 525.3 ± 12.8 μm in length and 94.9 ± 5.14 μm in width, with a length to width ratio of 5.54 ± 0.18. The anterior region of the egg is tubuliform, with a well-developed micropylar collar measuring approximately 2.54 ± 0.33 μm in thickness, the inner side of which is uniformly and deeply excavated, with a depression around the outer margin of the micropylar disc, which has a diameter of 29.4 ± 1.7 μm, an area of 234.4 μm2 ± 401.3 μm2 and a slightly elevated central region measuring 1.7 ± 0.5 μm in diameter that bears the central micropyle.